PEMBELAJARAN TARI KREASI MOLABOT MENGGUNAKAN MODEL INKUIRI TERBIMBING PADA SISWA KELAS IX-A MTSN 2 BANGGAI - Lumalaga, Khusnul; Djafar, Nurlia; Samiaji, Trubus; Sitharesmi, Riana Diah; Ohi, Rahmawati (SINERGI : Jurnal Riset Ilmiah, 2025)
This research is based on problems that occur in the dance learning process in class IX A MTSN 2 Banggai. In this case, in accordance with the 2013 curriculum, the basic competency in creative dance material in class IX is that students are expected to be able to understand and demonstrate creative dance movements based on the supporting elements of dance. However, in dance learning in class IX-A the teacher only assigns students to note down the material in the textbook, whereas in learning to demonstrate creative dances the teacher can provide examples of dances originating from their own region, namely the Molabot dance creations, which can be taught to student. Given these problems, researchers used the Guided Inquiry model as an alternative to help teachers in the learning process. The aim of this research is to describe the learning process using the Guided Inquiry Model for grade 9 students with dance material created by Molabot at MTSN 2 Banggai. Based on the results of Molabot's creative dance learning using the Guided Inquiry model, it shows that of all class IX A MTSN 2 Banggai students, totaling 17 students, there were 8 students who got a grade of A (Very Good), 6 students who got a grade of B (Good), and 3 students who students who get a grade of C (Adequate). So the average student score was 80.58 and the percentage result was 82% and met the criteria B (Good). In the practical evaluation carried out per group, there were 2 groups and each received a grade of B (Good).